Modeling Heavy Metal Behavior in Sustainable Drainage Systems: A Case Study. Issue 2 (8th November 2013) - Quinn, Ruth; Dussaillant J., Alejandro
<x xml:space="preserve">Abstract</x> A major problem of increased urbanization is the rise in pollution caused by run‐off. Among alternative management strategies, the use of sustainable drainage systems (SuDS) such as rain gardens and other bioretention facilities is becoming an increasingly attractive option to reduce these problems. However, there are few tools if any available for their design considering pollutant retention. In this paper, a dual‐permeability based model that predicts the fate of heavy metals in SuDS is presented, and applied to the design of a rain garden system for a planned roundabout in Kent, UK. Preliminary design considered an upper root zone layer with organic soil and a sandy storage sub‐layer, each 30 cm thick, for a bioretention area of 5 and 10% the size of the contributing impervious surface. Two scenarios are examined: the accumulation and movement of metals without macropores and the possibility of groundwater contamination due to preferential flow. It is shown that levels of lead can build up in the upper layers of the system, but only constitute a health hazard (surpass UK standard of 750 mg/kg) after 10 years. Simulations show that copper was successfully retained (no significant concentrations below 50 cm of rain garden soil depth). Finally, given concerns of preferential flow bypassing bioretention facilities, macropore flow was examined. Results indicated that due to site conditions it was not a threat to groundwater in the timeframe considered.